PSVIII-41 Unique Signatures of Galectin Expression in Cow Blood Exposed to Microbial Cell Wall Antigens. (7th December 2018) - Asiamah, E; Ekwemalor, K; Adjei Fremah, S; Worku, M; Osei, B
Abstract: This study evaluates the impact of lipopolysaccharide (LPS) derived from the cell wall of the Gram-negative bacteria Escherichia coli and, peptidoglycan (PGN) from the cell wall of the gram-positive bacteria Staphylococcus aureus on galectin gene expression in cow blood. Infection by these pathogens and the immune response to pathogen-associated molecular patterns (PAMPS) such as LPS and PGN is associated with infectious and metabolic diseases in animals impacting health and production. Galectins are carbohydrate-binding proteins that when expressed play important roles in the resolution of infectious and metabolic diseases. Thus it is important to determine if Galectin gene expression in blood is affected by exposure to LPS and PGN. Blood was taken from 5 multiparous Holstein cows and incubated with 10 µg/mL of LPS or PGN at 37 o C, with 85% humidity and 5% CO2 for 30 minutes. Samples treated with PBS served as controls. Total RNA was isolated, reverse-transcribed to cDNA. Commercially sequenced cow Galectin specific primers were used for real-time PCR. GAPDH and beta-actin served as internal controls. Fold change in transcript abundance was calculated using the Livak method. Enzyme-linked immunosorbent assay was used to detect and determine the concentration of Galectins in plasma. Galectin secretion was analyzed with Proc GLM in SAS 9.4. LPS increased transcription of LGALS 4 and 12 (2.5 and 2.02 folds respectively) and decreased secretion of Gal 4 (P=0.04). PGN increased transcription of LGALS-1, -2, -3, -4, -7 and -1 2 (3, 2.3, 2, 4.1, 3.3, 2.4 folds respectively) and secretion of Gal-8 and Gal-9 (P=0.0001 and P = Thus, LPS and PGN differentially modulated transcription of mRNA and secretion of galectins. Further studies are needed on the significance of the observed unique signatures of these PAMPS to aid in the control of infectious and metabolic diseases.